Sustainable Warm-Climate Forage Legumes: Versatile Products and Services - James P. Muir; José C. Batista Dubeux Junior; Mércia V. Ferreira dos Santos; Jamie L. Foster; Rinaldo L. Caraciolo Ferreira; Mário de Andrade Lira; Barbara Bellows; Edward Osei; Bir B. Singh; Jeff A. Brady (Grasses, 2025)
Forage legumes, besides their use as ruminant feed supplements, contribute to other agricultural, forestry and natural ecosystems’ sustainability around the world. Our objective in this summary is to emphasize that versatility in the face of biotic, abiotic and socio-economic variability is among the most important traits that forage legumes contribute to sustaining human populations in those diverse ecosystems. Forage legumes could contribute even more to agroecosystems if we 1. consider ecosystem services as well as food, feed and fuel production; 2. more fully exploit what we already know about forage legumes’ multiple uses; and 3. focus greater attention and energy exploring and expanding versatility in currently used and novel versatile species. To draw attention to the importance of this versatility to sustainable grasslands, here we review multiple legumes’ roles as forage, bioenergy, pulses (legume seeds for human consumption), pharmaceuticals and cover crops as well as environmental services, in particular soil health, C sequestration and non-industrial organic N. The major points we single out as distinguishing sustainable versatile forage legumes include (1) multiple uses; (2) adaptation to a wide range of edaphoclimatic conditions; (3) flexible economic contributions; and (4) how genomics can harness greater legume versatility. We predict that, because of this versatility, forage legumes will become ever more important as climates change and human pressures on sustainable agro-environments intensify.